Hereditary leiomyomatosis and renal cell carcinoma syndrome: a case report and implications of early onset - Ercan Çaliskan; Serkan Bodur; Mustafa Ulubay; Ibrahim Özmen; Ali Fuat Çiçek; Güzin Deveci; Engin Kaya (Sociedade Brasileira de Dermatologia, 2017)
Abstract Hereditary leiomyomatosis and renal cell carcinoma (HLRCC) is an autosomal dominant manifestation of cutaneous and uterine leiomyomas together with renal cancer due to autosomal dominant germline mutations of fumarate hydratase gene. A twenty-year-old female patient presented with type-II segmental piloleiomyoma and increased menstruation due to uterine leiomyomas, with a history of bilateral nephrectomy performed at 13 and 16 years of age for type 2 papillary renal cell carcinoma. This case represents one of the very early onsets of hereditary leiomyomatosis and renal cell carcinoma syndrome. As genetic anticipation for renal cancer is a well-documented entity for HLRCC syndrome, early recognition is crucial for both the patient and her family in order to provide appropriate counseling and initiation of surveillance.